PATTERNS OF ADVERSE DRUG REACTIONS: A STUDY IN A TERTIARY CARE HOSPITAL - Mir, Shakeel Ahmad (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The purpose of this study was to describe the pattern of adverse drug reactions (ADRs) in a tertiary care hospital, as ADRs are among the most common causes of morbidity and mortality. Methods: This prospective study, which ran from January 2020 to December 2021, observed all patients admitted to the various departments of SKIMS Hospital Srinagar for the development of ADRs. Results: ADRs were found to be slightly more prevalent in female patients (54.82%) and those aged 40–60 years (30.11%). Antibiotics (64.3%), anticancer drugs (9.4%), and gastrointestinal tract (GIT) medications (7.3%) were most commonly associated with ADRs. The commonly involved system organs were the skin (69.9%), the nervous system (24.1%), the GIT (19.5%), and the respiratory system (15.6%). 8.0% of ADRs were serious. Conclusion: The prevalence of ADRs makes them a major concern. To ensure patient safety, active patient surveillance is critical to identifying and controlling ADRs.